Public-private partnerships in primary health care: a scoping review - Nasrin Joudyian; Leila Doshmangir; Mahdi Mahdavi; Jafar Sadegh Tabrizi; Vladimir Sergeevich Gordeev (BMC, 2021)
Abstract Background The Astana Declaration on Primary Health Care reiterated that PHC is a cornerstone of a sustainable health system for universal health coverage (UHC) and health-related Sustainable Development Goals. It called for governments to give high priority to PHC in partnership with their public and private sector organisations and other stakeholders. Each country has a unique path towards UHC, and different models for public-private partnerships (PPPs) are possible. The goal of this paper is to examine evidence on the use of PPPs in the provision of PHC services, reported challenges and recommendations. Methods We systematically reviewed peer-reviewed studies in six databases (ScienceDirect, Ovid Medline, PubMed, Web of Science, Embase, and Scopus) and supplemented it by the search of grey literature. PRISMA reporting guidelines were followed. Results Sixty-one studies were included in the final review. Results showed that most PPPs projects were conducted to increase access and to facilitate the provision of prevention and treatment services (i.e., tuberculosis, education and health promotion, malaria, and HIV/AIDS services) for certain target groups. Most projects reported challenges of providing PHC via PPPs in the starting and implementation phases. The reported challenges and recommendations on how to overcome them related to education, management, human resources, financial resources, information, and technology systems aspects. Conclusion Despite various challenges, PPPs in PHC can facilitate access to health care services, especially in remote areas. Governments should consider long-term plans and sustainable policies to start PPPs in PHC and should not ignore local needs and context.